Perancangan Media Promosi Cairo Water Sebagai Upaya Untuk Meningkatkan Brand Awareness - Muhammad Kholilullah; Ine Rachmawati; Yuni Awalaturrohmah Solihah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
There are currently many bottled drinking water products appearing on the market. This is closely related to the high public need for drinking water that is suitable for consumption. One of these drinking water products is Cairo Water. Cairo Water is in great demand by the people of Cirebon Regency, however currently, Cairo Water does not have promotional media.  This causes a less extensive market reach, weak brand awareness, and a threat to Cairo Water's ability to compete with its current competitors. Strategies that can be used to resolve the above problems include the Integrated Marketing Communication method, using an informative, persuasive, and reminding approach. The promotional media created aims to create interest in potential consumers, increase brand awareness, and also establish bonds with consumers. In this design, the author designs promotional strategies both offline and online. Offline promotional media in the form of designs on brochures, banners, posters, and vehicle signage. The online promotional media is in the form of feed design content via Instagram, Facebook, and TikTok. After completing the final design, the author tested the media by creating a questionnaire regarding respondents' assessments after seeing the promotional media and the results produced a very positive response.